Enhancing rate capability of amorphous nickel phosphate supercapattery electrode via composition with crystalline silver phosphate - Omar, Fatin Saiha; Numan, Arshid; Bashir, Shahid; Duraisamy, Navaneethan; Vikneswaran, Rajamuthy; Loo, Yueh Lin; Ramesh, Kasi; Ramesh, Subramaniam (Elsevier, 2018)
The performance of a supercapattery depends on its energy density, rate capability of charge and discharge and stability of electrode. Here in, a sonochemical method followed by calcination was applied to synthesize nickel phosphate-silver phosphate (Ni3(PO4)2–Ag3PO4) nanocomposites. Morphological studies revealed that crystalline Ag3PO4 (∼10 nm) was intimately anchored on the surface of amorphous Ni3(PO4)2, which benefits efficient charge transfer between the two metal phosphates. The optimized Ni3(PO4)2–Ag3PO4 nanocomposite electrode exhibited a significant boost in rate capability from 29% (Ni3(PO4)2) to 78% capacity retention with the maximum specific capacity of 478C/g at 1 A/g in 1 M KOH electrolyte. The enhancement of rate capability originated from a more rapid electron-transfer rate and an augmentation of electroactive sites for electrolyte ion diffusion from the interfaces of porous Ni3(PO4)2 and an improvement in the electrical conductivity of crystalline Ag3PO4. The fabricated Ni3(PO4)2–Ag3PO4//activated carbon-based supercapattery exhibited an energy density of 32.4 Wh/kg at 399.5 W/kg and excellent cyclic stability (∼82% capacity retention after 5000 cycles).